Microstructure and kinetic evolutions of multi-variants lamella in γ-TiAl alloys - Zan Zhang; Jicheng Zhuo; Kunning Niu; Peng Sang; Shenglong Wang; Haiwei Zhang; Yongsheng Li (Materials & Design)
The D019-α2 / L10-γ alternate lamellae microstructure in TiAl alloys brings the superior mechanical property, the lamellae with multi-variant γ phase are key characteristic of morphology-property causality. The nucleation, growth and coarsening of multi-variants γ are investigated in TiAl alloys by using the three-dimensional phase-field simulation, the γ morphology, lamellar spacing (LS) and the predicted yield strength of alloy are in agreement with the experiment. It is found that the γ variants can nucleate and grow up separately to form the single-variant lamella, or through the symbiotic nucleation and growth to form multi-variant lamella, the growth of γ lamella follows the terrace-ledge-kink mechanism. The growth rate along the longitudinal direction is distinctly larger than that of the thickness direction, resulting in the lamellar structure. A three-stage growth kinetics, nucleation, growth and coarsening of γ lamella in thickness is revealed. As Al content changes, the LS is enlarged with the reduced lamella number. The influence of the LS on the mechanical properties is evaluated by using the Hall-Petch relationship. The results give an insight for the formation and evolution mechanisms of multi-variant γ lamella, and discover the internal relations of lamellar morphology and mechanical properties of TiAl alloys.